Advances on inorganic scintillator-based optic fiber dosimeters - Ding, Liang (EJNMMI Phys, 2020)
This article presents a new perspective on the development of inorganic scintillator-based fiber dosimeters (IOSFDs) for medical radiotherapy dosimetry (RTD) focusing on real-time in vivo dosimetry. The scintillator-based optical fiber dosimeters (SFD) are compact, free of electromagnetic interference, radiation-resistant, and robust. They have shown great potential for real-time in vivo RTD. Compared with organic scintillators (OSs), inorganic scintillators (IOSs) have larger X-ray absorption and higher light output. Variable IOSs with maximum emission peaks in the red part of the spectrum offer convenient stem effect removal. This article outlines the main advantages and disadvantages of utilizing IOSs for SFD fabrication. IOSFDs with different configurations are presented, and their use for dosimetry in X-ray RT, brachytherapy (BT), proton therapy (PT), and boron neutron capture therapy (BNCT) is reviewed. Challenges including the percentage depth dose (PDD) deviation from the standard ion chamber (IC) measurement, the angular dependence, and the Cherenkov effect are discussed in detail; methods to overcome these problems are also presented.